CITES makes a measurable difference to the trade in live marine fishes: The pioneering case of seahorses. (August 2022) - Foster, S.J.; Justason, T.; Magera, A.M.; Vincent, A.C.J.
Abstract: Seahorses set precedent as the first marine fishes added to CITES Appendix II and taken through CITES processes. Although the vast majority of seahorses are traded dead for traditional medicine, the live trade for ornamental display was the main pressure on some populations. We investigated changes in the international trade in live seahorses over time, exploring the influence of CITES listing and its compliance process (called Review of Significant Trade or RST). Globally, reported exports of live seahorses from key trading Parties declined notably in the first years after the CITES listing, and yet more after RST, to just 7 % of historic levels. These changes are explained first by a decline in wild sourcing after the listing and then by a decrease in the number of captive born seahorses (from wild-sourced parents) after RST. Almost all live seahorses in international trade are now captive bred (F2 generation or more). Consequently, there are now fewer wild sourced species in trade, from fewer countries and more tank-raised species, from more countries. In summary, the CITES listing for seahorses appears to have reduced pressure of international trade on some wild populations – those involved in live trade. This gain is, however, tiny in the context of the vast trade in dried seahorses, most of which are now smuggled across borders. The difference probably lies in the small volume and relatively high value of the aquarium trade. CITES Parties still need to determine how changes in live trade are affecting wild seahorse populations. Highlights: Listing seahorses on CITES has changed the live trade in two significant ways. 1) Volumes of seahorses in international trade have declined considerably over time. 2) The international trade has seen a shift from wild to captive bred sourcing. In contrast, the dried seahorses trade remains problematic after the CITES listing. We do not know how changes in live trade are affecting wild seahorse populations.